Relationship Between Low Relative Muscle Mass and Coronary Artery Calcification in Healthy Adults - Ko, Byung-Joon; Chang, Yoosoo; Jung, Hyun-Suk; Yun, Kyung Eun; Kim, Chan-Won; Park, Hye Soon; Chung, Eun Chul; Shin, Hocheol; Ryu, Seungho (Arteriosclerosis, thrombosis, and vascular biology, 2016)
OBJECTIVE—Sarcopenia or low muscle mass is related to cardiovascular risk factors; however, the association between low muscle mass and subclinical atherosclerosis has been largely unexplored. We investigated whether muscle mass is related to coronary artery calcification (CAC) in a large sample of middle-aged asymptomatic adults. APPROACH AND RESULTS—We performed a cross-sectional study of 31 108 asymptomatic adults without cancer, diabetes mellitus, or known cardiovascular disease who underwent a health checkup examination including cardiac tomography estimation of CAC scores between 2012 and 2013. Skeletal muscle mass index (SMI) [SMI (%)=total skeletal muscle mass (kg)/body weight (kg)×100] was estimated using a bioelectrical impedance analyzer. We assessed the relationship between SMI and CAC scores using both multivariate-adjusted Tobit models and multinomial logistic regression models. Of the 31 108 subjects, 3374 subjects (10.9%) had a CAC score 1 to 100, and 628 subjects (2.0%) had a CAC score >100. SMI was inversely associated with CAC score ratios. Specifically, in a multivariable-adjusted model adjusting for potential confounders, CAC score ratios (95% confidence intervals) of SMI for quartiles 1, 2, and 3 compared with quartile 4 were 2.27 (1.70–3.05), 1.46 (1.15–1.85), and 1.24 (0.98–1.55), respectively (P for trend <0.001). Adjusting for insulin resistance reduced the magnitude of the associations, but they remained statistically significant. CONCLUSIONS—Relative muscle mass was negatively associated with the prevalence of coronary calcification, supporting low muscle mass as an independent risk factor of coronary heart disease.